Effect of iron supplementation on mental and motor development in children: systematic review of randomised controlled trials - Sachdev, H. P. S.; Gera, Tarun; Nestel, Penelope (Cambridge University Press, 2005)
Objective To evaluate the effect of iron supplementation on mental and motor development in children through a systematic review of randomised controlled trials (RCTs).